1994
DOI: 10.1063/1.868308
|View full text |Cite
|
Sign up to set email alerts
|

From Reynolds’s stretching and folding to mixing studies using horseshoe maps

Abstract: Osborne Reynolds’s seminal idea of stretching and folding being the basis of fluid mixing has a direct bearing on the interpretation of mixing processes involving dynamical systems tools, in particular, horseshoe maps. Horseshoes offer the only direct, mathematically rigorous, experimental verification of chaos in a flow. In this work these ideas are formalized and developed, with the goal of exploiting the concepts in experimental mixing studies, particularly in the case of alternating doubly symmetric flows.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 16 publications
1
45
0
1
Order By: Relevance
“…with corresponding symmetry axis I 1 = S 2 I 1 the reflection of I 1 about I 2 (Ottino et al 1994;Speetjens et al 2004). Figure 6 gives the symmetry axes I 1 (red), I 1 (green), I 2 (blue) corresponding with the set of time-reversal symmetries (S 1 , S 1 , S 2 ) for the Poincaré sections at Θ = 3π/4 and T step = 0.2.…”
Section: Symmetry Within Sampling Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…with corresponding symmetry axis I 1 = S 2 I 1 the reflection of I 1 about I 2 (Ottino et al 1994;Speetjens et al 2004). Figure 6 gives the symmetry axes I 1 (red), I 1 (green), I 2 (blue) corresponding with the set of time-reversal symmetries (S 1 , S 1 , S 2 ) for the Poincaré sections at Θ = 3π/4 and T step = 0.2.…”
Section: Symmetry Within Sampling Levelsmentioning
confidence: 99%
“…Hence, said symmetries are key to shape and arrangement of the islands and thus play an essential role in the entrapment of production fluid. Moreover, the co-existence of multiple time-reversal symmetries implies periodic points Φ(x) = x at intersections of their symmetry axes (Ottino et al 1994). Thus the elliptic point upon which the predominant island is centred, e.g.…”
Section: Symmetry Within Sampling Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments with channels with complex surface topology including grooved walls have revealed that microscale mixing is enhanced by ''chaotic advection'', a process which was first reviewed by Aref (1984). He describes how mixing is still possible even at low Reynolds number by repeated stretching and folding of fluid elements (Ottino et al 1994). If properly applied, this mechanism causes the interfacial area between the fluids to increase exponentially, which can then lead to an enhanced intermaterial transport, hence mixing.…”
Section: Introductionmentioning
confidence: 99%
“…If properly applied, this mechanism causes the interfacial area between the fluids to increase exponentially, which can then lead to an enhanced intermaterial transport, hence mixing. A comprehensive mathematical description of the exponential growth of interfacial surfaces can be found in the book by Ottino (1989). Mixers, which utilize the principle of ''chaotic advection'', were designed in the following years (Kim 2007).…”
Section: Introductionmentioning
confidence: 99%